Risk of Burnout among Younger Health Quarantine Workers in Indonesia - Ratih Catur Sholihah; Dewi Sumaryani Soemarko; Amilya Agustina; Retno Wibawanti; Nuri Purwito Adi (The Indonesian Journal of Community and Occupational Medicine, 2026)
Introduction: Burnout is a work-related stress condition commonly associated with long working hours and high job demands, making health quarantine workers particularly vulnerable. Evidence on the role of age in burnout is inconsistent, although older workers are often assumed to be at higher risk. This study investigates the relationship between age and burnout among health quarantine workers to determine which age group is more prone to burnout and to provide evidence that can guide early preventive interventions. Methods: A cross-sectional study was conducted in September–October 2025 using secondary data from a survey by PT Y. Burnout was measured using the Maslach Burnout Inventory (MBI) questionnaire. Results: Burnout prevalence among health quarantine workers was 25.4%. Multivariate analysis showed a p-value of 0.049 for age. Statistical tests showed p-values > 0.05 for the relationships between gender, education level, marital status, having children under five years old, work patterns, length of service, work area, employment status, or commuting distance with overall burnout. Conclusion: More than one-fourth of health quarantine workers experienced burnout, with younger workers showing the highest risk. Age was the strongest predictor of burnout, indicating greater vulnerability among younger staff. Targeted support for early-career workers is essential to reduce burnout risk and strengthen workforce well-being.